EFL STUDENTS’ PERCEPTIONS ON THE USE OF LIVEWORKSHEETS AS TEACHING AND LEARNING PLATFORM - Alfiana, Nuraviah (Premise: Journal of English Education and Applied Linguistics, 2023)
This study aims to provide comprehensive insights into EFL students' perceptions of using the live worksheets as a teaching and learning platform. The study involved 8-grade students at Al-Ikhlas Excellent Junior High School Rembang, consisting of 9 female and five male students. This study conducted the case study design by using the descriptive statistics method. Surveys and interviews were conducted to gather students' opinions and feedback regarding their experiences with live worksheets. The survey explored aspects such as ease of use, usefulness, satisfaction, and benefits of the live worksheets’ platform in EFL learning. The interviews provided more profound insights into students' perceptions and experiences. The data will be statistically analyzed using descriptive techniques. The result indicated that 78,6% of students had utilized live worksheets for their assignments. From the frequency of use, it was found that 57.1% of students formed their first impressions of Live worksheets through this research, while 50% found it to be well-suited to their needs. Impressively, 85.7% of students reported enjoying the platform. Furthermore, the Likert scale shows that 71,4% of students feel this platform is easy to access. 78,5% of students say this platform has a fascinating display. Then, 78,5% of students convey that this platform has various tasks. In conclusion, Live worksheets emerged as an efficient teaching and learning platform. It was found to be easily accessible, visually appealing, and diverse in its range of tasks, making it a valuable tool for EFL education. Hopefully, this study contributes to the existing literature on technology integration in language education and provides practical insights for educators, curriculum developers, and platform designers.